Development of cellulose nanofibrils reinforced polyvinyl alcohol films incorporated with alizarin for intelligent food packaging - Chen, Hui‐zhi; Zhang, Min; Rao, Zhiming (International journal of food science & technology, 2021)
Summary Visual pH‐sensing films were fabricated using cellulose nanofibrils (CNF) reinforced polyvinyl alcohol (PVA) and alizarin. The relationships between the ratio of PVA: CNF hydrogel (2:1, 1:1, 1:2) and the physical properties and colour response efficiency of indicator films were investigated. Fourier transform infrared spectroscopy of films evidenced alizarin and CNF was properly incorporated by physical interaction. A new weak X‐ray diffraction peak appeared at 2θ = 22.4°, which was affected by the incorporation of CNF. The increase in the CNF content induced enhancements of thermal stability, tensile strength, water contact angle and colour sensitivity of the indicator films. The colourimetric films had a higher sensitivity to discolouration when exposed to acidic vapours than alkaline vapours. The films presented a remarkable colour change varied from purple in alkaline condition to yellow in acidic condition. Therefore, this colourimetric film can be used as a volatile acid sensor for intelligent packaging. Visual pH‐sensing films were fabricated using cellulose nanofibrils (CNF) reinforced polyvinyl alcohol (PVA) and alizarin. The relationships between the ratio of PVA: CNF hydrogel and the physical properties and colour response efficiency of indicator films were investigated.